Hukuman Mati dalam Tindak Pidana Narkotika Ditinjau dari Perspektif Hak Asasi Manusia (Studi Putusan Mahkamah Konstitusi Nomor 2-3/Puu-V/2007 - Christofel Brayn Leonard Totomutu; I Ny Oman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2021)
The capital punishment is regulated in several laws and regulations in Indonesia, in particular for narcotics crimes that are submitted for judicial review against the Constitution. The type of research used is the type of normative. The sources of the data used in this research are primary, which are taken from the original source of the law and secondary materials are materials derived from books, journals and scientific works and tertiary legal materials. The technique of collecting data in this research is carried out by collecting existing materials or studying documents from existing laws and regulations as well as the decisions of the constitutional court judges and explaining the sentence by using the legal material processing method systematically. The purpose of this research was to determine the capital punishment for narcotics crime in terms of human rights and to find out the judges considerations on the capital punishment for narcotics crime in Indonesia based on the decision of the constitutional court number 2-3/PUU-V/2007. The results of the research revealed that the capital punishment for narcotics crime has been stated in articles and laws, but on the other hand there is a consideration of the panel of judges regarding the capital punishment case for narcotics crime that the capital punishment in the Narcotics Law does not contradict human rights and human rights as in the 1945 Constitution of the Republic of Indonesia because the guarantee of human rights and the right to life in the 1945 Constitution of the Republic of Indonesia does not adhere to absolute principles.